Análise de movimentos periódicos em sistemas com vibro-impacto harmonicamente excitados - Barbosa, Danilo de Almeida (2009)
As mechanical systems become more flexible new phenomena of dynamic systems, before less important because of the low probability of its occurrence, gain importance. Among these are systems with vibro-impacts. Is that the Systems more flexible end up amplifying the phenomena that occur during the impacts and there is contribution these phenomena in the dynamics of the global system. This paper presents a study on systems with vibro-impact, taking as an object of particular study a mass-spring-damper excited by the base, whose movement is laterally limited by obstacles against which the moving mass collides. The system is analyzed in its dimensionless form where our research focuses on studying the conditions of existence and stability of certain types of movement. The exhaustive search of the existence and of the stability of many standard of movement is not the objective this your work. We will only describe in detail the technical and computational tools that can facilitate work like is. After this step, we present some analysis to the movement patterns most common, with interesting conclusions.